2015
DOI: 10.1556/achrom.27.2015.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fructus Arctii from Different Regions of China by HPLC Coupled with Chemometrics Methods

Abstract: Summary.To evaluate the quality of Fructus Arctii, an accurate and reliable method of high-performance liquid chromatography/diode array detection-electrospray ionization-mass spectrometry (HPLC/DAD-ESI-MS) was developed. Nine compounds, including chlorogenic acid, caffeic acid, trans-p-hydroxycinnamic acid, arctiin, arctignan A, ethyl caffeate, matairesinol, arctigenin, and lappaol B, were determined simultaneously in 19 batches of Fructus Arctii samples collected from different localities. Nineteen common pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These pure compounds were then characterized by MS and NMR spectra. Based on comparison of the spectral data with the literature values , the results showed that they were all lignans with similar structures. The data of structure, purity and weight of compounds was listed in Table and the NMR and MS data are illustrated in the Supporting Information.…”
Section: Resultsmentioning
confidence: 91%
“…These pure compounds were then characterized by MS and NMR spectra. Based on comparison of the spectral data with the literature values , the results showed that they were all lignans with similar structures. The data of structure, purity and weight of compounds was listed in Table and the NMR and MS data are illustrated in the Supporting Information.…”
Section: Resultsmentioning
confidence: 91%
“…It was reported in the literature that the RSD of the peak area of the characteristic peak was less than 3%, which meant that the method met requirements of fingerprint analysis. [ 40 ] Therefore, the established chromatography method could be used for the quality evaluation of camellia oil.…”
Section: Resultsmentioning
confidence: 99%
“…After reducing dimensions, every sample obtained a score plot and based on the score plot, a classification was made . HCA is an intuitive classification method, dividing samples into categories according to the similar distance degree (in this study, the single linkage method was used) . These two methods could support each other to some degree.…”
Section: Methodsmentioning
confidence: 99%